Nemška kolonizacija kamniškega okrožja v letih 1941–1945 - Hančič, Damjan (Časopis za zgodovino in narodopisje, 2023)
In the present article, the author complements the existing basic research on the German colonisation of the Kamnik area during the occupation during the Second World War with additional archival material discovered in this regard. The German colonisation, which constituted only one of the many humiliating measures taken by the German occupier in the area, took place in two phases: in the first months after the occupation, the German occupier settled mainly German officials, clerks and teachers, while the second phase, which took place in the late summer and autumn of 1942, was less successful, with only 15 German farmers and their families settling on the previously Slovenian farms, yet they faced many difficulties.
Keywords: druga svetovna vojna; germanizacija; Kamnik; kolonizacija; okupacija; svetovna vojna 1939-1945